Identification and Characterization of Nine Novel X-Chromosomal Short Tandem Repeats on Xp21.1, Xq21.31, and Xq23 Regions - Yang, Qinrui; Qian, Jinglei; Shao, Chengchen; Yao, Yining; Zhou, Zhihan; Xu, Hongmei; Tang, Qiqun; Qian, Xiaoqin; Xie, Jianhui (Frontiers in Genetics, 2021)
The application of X-chromosomal STRs (X-STRs) has been recognized as a powerful tool in complex kinship testing. To support further development of X-STR analysis in forensic use, we identified nine novel X-STRs which could be clustered into three linkage groups (LGs) on Xp21.1, Xq21.31 and Xq23. A multiplex PCR system was build based on the electrophoresis. A total of 198 unrelated Shanghai Han samples along with 168 samples from 43 families was collected to investigate the genetic polymorphism and forensic parameters of the nine loci. Allele numbers ranged from 5 to 12 and amplicon sizes ranged from 146 bp to 477 bp. The multiplex showed high values for the combined power of discrimination (0.99997977 in males and 0.99999999 in females) and combined mean exclusion chances (0.99997918 and 0.99997821 in trios, 0.99984939 in duos, and 0.99984200 in deficiency cases). The linkage between all pairs of loci was estimated via Kosambi mapping function and linkage disequilibrium test, and further investigated through the family study. The data from 43 families strongly demonstrated an independent transmission between LGs and a tight linkage among loci within the same LG. All these results support that the newly described X-STRs and the multiplex system are highly promising for the further forensic use.